Predictive value of qSOFA score for mortality in older patients with dengue fever: a retrospective case-control study - Chi-Heng Lee; Yu-Chieh Ho; Chien-Chin Hsu; Hung-Jung Lin; Jui-Yuan Chung; Chien-Cheng Huang (BMC Geriatrics)
Abstract Background Dengue fever (DF) in older patients is associated with higher mortality, but optimal mortality prediction approaches remain unclear. We assessed the utility of the quick Sequential Organ Failure Assessment (qSOFA) as a predictive tool in older DF patients. Methods We retrospectively included DF patients aged ≥ 65 years who visited our study hospital between September 1, 2015, and December 31, 2015. Demographics, vital signs, comorbidities, laboratory data, and mortality were collected. Accuracy of qSOFA score ≥ 2 in predicting 30-day mortality was evaluated. Results 626 older DF patients were recruited (mean age: 74.1 years, nearly equal sex distribution). Mean ± standard deviation of qSOFA score was higher in mortality group vs. survival group (0.6 ± 0.8 vs. 0.1 ± 0, p < 0.01). Logistic regression showed qSOFA score ≥ 2 associated with higher mortality risk (odds ratio: 18.74; 95% confidence interval: 4.37 − 50.64). Adjusted area under receiver operating characteristic was 0.75, and Hosmer-Lemeshow goodness of fit test was 0.58. Sensitivity, specificity, positive predictive value, and negative predictive value of qSOFA score ≥ 2 for predicting mortality were 18.5%, 98.7%, 38.5%, and 96.4%, respectively. Conclusion qSOFA score ≥ 2 is a simple and specific tool for predicting 30-day mortality in older patients with DF, with high specificity and negative predictive value. It can be used to rule out patients at high risk of mortality.